Islamic Values-Oriented Math Modules with Discovery Learning Model: Validity, Practicality, and Effectiveness - Nur Kamila, Novianti; Aini, Afifah Nur (Contemporary Education and Community Engagement (CECE), 2026)
The unavailability of adequate learning modules can lead to suboptimal student learning outcomes. Therefore, this research aims to design an Islamic values-oriented math module using the Discovery learning model. The development stage refers to the 4-D model, which includes: define, design, develop, and disseminate. In the define stage, a curriculum analysis and student needs assessment are conducted. In the design stage, the module is designed. In the develop stage, validity tests are conducted, including the validity of Islamic content, language, math content, and media. In the disseminate stage, a field trial is conducted at MA Annuriyah. The module validity test results were 87.5%, 88.6%, 90%, and 82.8%, respectively, in the aspects of math content, Islamic values, language, and media. The practicality test results showed a score of 83.1%, categorized as very practical. The effectiveness test results showed a significant difference in pre-test and post-test scores with a sig. 0.00 < 0.05 and an average increase from 21.88 to 87.20. It was concluded that the developed math module was proven to be valid, practical, and effective.